Case Report: A unique case of secondary hemophagocytic lymphohistiocytosis from ehrlichiosis infection - Hlaing, Swe Swe; Kurian, Christine Jane; Tan, Jennie; Behling, Eric; Hussein, Ahmed Kamel Abou (Frontiers in Hematology, 2022)
Hemophagocytic Lymphohistiocytosis (HLH) is a highly detrimental syndrome that can lead to a 40% mortality rate often progressing to multiorgan failure, requiring the resources of an intensive care unit. Secondary HLH is usually triggered by infection, mostly from a viral infection or malignancies. Management of HLH in adults is challenging as treatment algorithms targeting hyperinflammation are based on pediatric protocols, such as HLH-94 and HLH-2004. To our knowledge, there are only a few cases of HLH secondary to Ehrlichiosis infections, but none in elderly patients with multiple comorbidities. Here, we present a unique case of HLH in an 82-year-old female secondary to Ehrlichiosis infection, successfully treated with antibiotics and steroids.